2009
DOI: 10.5465/amle.2009.37012177
|View full text |Cite
|
Sign up to set email alerts
|

Power, Safety, and Learning in Racially Diverse Groups

Abstract: We propose that power inequities drive dynamics in racially diverse teams, often leading to conflict, withdrawal, or assimilation-all of which can impede team learning. We suggest several elements to address these dynamics, including identity safety or the belief that one is safe despite one's racial identity; a perspective that values cultural identity as a resource for thinking about work; and a welcoming stance toward new information and differing opinions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(34 citation statements)
references
References 119 publications
(147 reference statements)
0
34
0
Order By: Relevance
“…As a result, they behave in more tentative and inhibited ways that do not lend themselves to collective learning (Foldy, Rivard, & Buckley, 2009). So, for example, Nembhard and Edmondson (2006) found that the lower-status members of neonatal intensive care units (nurses and respiratory therapists) reported lower levels of psychological safety than higherstatus members (physicians) and, as a result, were less involved in learning.…”
Section: Power Status Risk-taking and Experimentationmentioning
confidence: 99%
“…As a result, they behave in more tentative and inhibited ways that do not lend themselves to collective learning (Foldy, Rivard, & Buckley, 2009). So, for example, Nembhard and Edmondson (2006) found that the lower-status members of neonatal intensive care units (nurses and respiratory therapists) reported lower levels of psychological safety than higherstatus members (physicians) and, as a result, were less involved in learning.…”
Section: Power Status Risk-taking and Experimentationmentioning
confidence: 99%
“…Other research has focused on the difficulties that arise as a result of power inequalities and diversity in groups. However, whilst power inequalities are suggested to impede group learning (Foldy et al 2009), the impact of group diversity on group performance remains contested (Shaw and Barrett-Power 1998;Orlitzky and Benjamin 2003). Looking at groups within both educational and organisational contexts, some authors suggest that group diversity has a positive effect on performance generally (McGrath 1984;McLeod and Lobel.…”
Section: Literature Reviewmentioning
confidence: 96%
“…Research in various disciplines suggest that individuals who perceive threats are likely to react defensively in order to reaffirm their social identity, restore justice, or deter future threats (Aquino & Douglas, 2003). Defensive strategies may manifest in overtly aggressive forms such as negative stereotyping and discrimination (Hornsey & Hogg, 2000), conflict or resistance (Jehn, 1995), criticism of one's abilities, and public humiliation (Aquino & Douglas, 2003), or less obvious forms such as physical or psychological withdrawal (Foldy, Rivard, & Buckley, 2009) decreased commitment (Purdie-Vaughns, Davies, Steele, Ditlmann, & Crosby, 2008), and in-group solidarity (Geddes & Konrad, 2003). With ITR, Petriglieri (2011) offered a framework that synthesized these literatures and provided a coherent explanation of the appraisal process and how people respond to identity threats and the likely consequences of those threats.…”
Section: Theoretical Development and Propositionsmentioning
confidence: 99%